Floor finish plans of BRAC University New Campus for RAJUK (Architectural As Built Drawings) - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2024)
This record contains architectural as-built drawings of Brac University New Campus Project. It consists of DWG version of drawings.